On Cyclically Continuous Edge Colorings of Trees - Kamalian, Rafayel R. (Mathematical Problems of Computer Science, 2021)
A cyclically continuous edge coloring of a graph is defined. For an arbitrary tree the existence of this coloring is proved and all possible numbers of colors in such colorings are found.